2016
DOI: 10.1021/acs.jproteome.5b00217
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bile Acids Are Associated with Pathological Progression of Hepatitis B-Induced Cirrhosis

Abstract: Recent metabonomic studies have identified an important role of bile acids in patients with liver cirrhosis. Serum bile acids, such as glycocholate (GCA), glycochenodeoxycholate (GCDCA), taurocholate (TCA) and taurochenodeoxycholate (TCDCA), increased significantly in liver cirrhosis patients. Our recently published urinary metabonomic study showed that glycocholate 3-glucuronide, taurohyocholate, TCA, glycolithocholate 3-sulfate and glycoursodeoxycholate (GUDCA) were markedly increased in hepatitis B-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 44 publications
10
67
1
Order By: Relevance
“…The changes of bile acid profiles in different liver conditions are inconsistent . Growing evidences suggested that cirrhosis is closely related with bile acid metabolism . In this study, we observed the increased amount of BAs in the serum of CHB patients with the progression of fibrosis.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The changes of bile acid profiles in different liver conditions are inconsistent . Growing evidences suggested that cirrhosis is closely related with bile acid metabolism . In this study, we observed the increased amount of BAs in the serum of CHB patients with the progression of fibrosis.…”
Section: Discussionsupporting
confidence: 47%
“…According to Genta et al, cirrhotic patients have been shown to have a higher serum primary BAs and the proportions of secondary BAs in bile were lower in advanced cirrhosis . A study performed by Wang et al showed that serum BAs are related with CHB‐induced cirrhosis …”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that the dysbiosis or elevated BA levels may produce substantial hepatic toxicities including a variety of cellular disorders, leading to sustained liver injury. Most importantly, our study on BAs showed that TCA, TCDCA, GCA and GCDCA were the most abundant BAs in blood and significantly increased in patients with cirrhosis and HCC …”
mentioning
confidence: 75%
“…The BA levels in plasma, liver, and feces were quantitatively measured by ultra‐performance liquid chromatography triple quadrupole mass spectrometry (UPLC‐TQMS) according to our previously reported protocol . All separations were performed with an ACQUITY BEH C18 column (1.7 µm, 100 mm × 2.1 mm internal dimensions) (Waters, Milford, MA) (Supporting Information Table 1).…”
Section: Measurement Of Serum Alt and Astmentioning
confidence: 99%
“…With the injury to liver cells, the creatinine clearance rate of bile acid declines, resulting in an increase in serum bile acid. Thus, bile acid is considered to be a biomarker of hepatic injury [37]. Taurocholic acid is a product of the combination of taurine in liver and bile acid.…”
Section: Discussionmentioning
confidence: 99%